2014
DOI: 10.2337/db14-0646
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Controls Circadian Hepatic Glucose Metabolism Through Heme Synthesis

Abstract: The circadian rhythm of the liver maintains glucose homeostasis, and disruption of this rhythm is associated with type 2 diabetes. Feeding is one factor that sets the circadian clock in peripheral tissues, but relatively little is known about the role of specific dietary components in that regard. We assessed the effects of dietary iron on circadian gluconeogenesis. Dietary iron affects circadian glucose metabolism through heme-mediated regulation of the interaction of nuclear receptor subfamily 1 group d memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
1
35
1
1
Order By: Relevance
“…Our results suggest that this may be a direct result of adipocyte iron loading, even within the physiologic range. In the mouse studies, as we have previously reported, the low normal-and high normal-iron diets represent the range of iron content seen in normal chows, and the high-iron diet does not cause overt iron pathology and results in increases in hepatic iron within the ranges seen in normal humans (44). Likewise, in the cell culture models, addition of iron to cells results in modulation of the transferrin receptor in a manner that mirrors normal iron physiology ( Figure 2A and Supplemental Figure 5C).…”
Section: Discussionmentioning
confidence: 81%
“…Our results suggest that this may be a direct result of adipocyte iron loading, even within the physiologic range. In the mouse studies, as we have previously reported, the low normal-and high normal-iron diets represent the range of iron content seen in normal chows, and the high-iron diet does not cause overt iron pathology and results in increases in hepatic iron within the ranges seen in normal humans (44). Likewise, in the cell culture models, addition of iron to cells results in modulation of the transferrin receptor in a manner that mirrors normal iron physiology ( Figure 2A and Supplemental Figure 5C).…”
Section: Discussionmentioning
confidence: 81%
“…Dietary iron seems to affect circadian gluconeogenesis and glucose metabolism by influencing the hememediated regulation of two important molecules: the nuclear receptor subfamily 1 group d member 1 and its cosuppressor nuclear receptor corepressor 1. When heme synthesis was blocked by the administration of aminolevulinic acid, variations in dietary iron did not affect hepatic glucose production or expression of gluconeogenic enzymes (26).…”
Section: Dietary Iron and The Circadian Clockmentioning
confidence: 99%
“…In turn, elevated heme leads to NCoR1 recruitment to Rev-erb␣ and repression of key enzymes involved in gluconeogenesis, ultimately lowering serum glucose concentrations. Thus, dietary signals like iron control metabolism through the regulation of core clock protein expression and heme biosynthesis (108).…”
Section: An Unknown Factor Present In Cell Extracts Mediates the Effementioning
confidence: 99%